2018
DOI: 10.17509/ijal.v7i3.9809
|View full text |Cite
|
Sign up to set email alerts
|

The Esl Teachers’ Willingness to Communicate in English

Abstract: Willingness to communicate (WTC) as introduced by McCroskey and Bear (1985) has developed and been perceived by many as a critical field. Unfortunately, there is a noticeable gap in research on the willingness to communicate (WTC) in English among ESL teachers in the Malaysian context. This study aims to investigate the ESL teachers' willingness to communicate in English in terms of gender and school locations. The four constructs of communication in WTC are group discussions, interpersonal, public, and talkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Next study was from Lo (2018) who examined ESL Teachers' willingness to communicate in English. One of the aims of this study was to determine the effect of gender and school location on the willingness to communicate (WTC) in English among ESL teachers.…”
Section: Measuring Willingness To Communicatementioning
confidence: 99%
See 1 more Smart Citation
“…Next study was from Lo (2018) who examined ESL Teachers' willingness to communicate in English. One of the aims of this study was to determine the effect of gender and school location on the willingness to communicate (WTC) in English among ESL teachers.…”
Section: Measuring Willingness To Communicatementioning
confidence: 99%
“…in English about it. In this study, Lo (2018) has four research constructs including discussion in groups, interpersonal, public, and speaking in meetings. participation in this study through criteria and convenience sampling, as many as 250 ESL teachers from twenty-five schools.…”
Section: Measuring Willingness To Communicatementioning
confidence: 99%
“…He also added that it was necessary to conduct more research on the fluctuation in WTC in English for teachers and students as well. The second study on teachers' WTC in English by Lo (2018) involved 250 Malaysian English teachers. Drawing on McCroskey and Baer's (1985) construct of WTC in English that includes talking in a group, personal traits, speaking in public, and using English in the classroom, Lo (2018) found that most participants' WTC in English were high in the professional settings rather than in public.…”
Section: Fluctuations In Willingness To Communicate Of An Efl Lecturer: An Observation Study In Indonesiamentioning
confidence: 99%
“…The second study on teachers' WTC in English by Lo (2018) involved 250 Malaysian English teachers. Drawing on McCroskey and Baer's (1985) construct of WTC in English that includes talking in a group, personal traits, speaking in public, and using English in the classroom, Lo (2018) found that most participants' WTC in English were high in the professional settings rather than in public. However, female participants tended to have higher WTC in public rather than the male ones.…”
Section: Fluctuations In Willingness To Communicate Of An Efl Lecturer: An Observation Study In Indonesiamentioning
confidence: 99%
“…The pressing need for L2 teachers to be willing to communicate in English is not only evident in the CLIL context (Aiello et al, 2017) but also in the ESL setting, in which English is used as the primary means of communication in studying many subjects from primary through higher education (Fahim & Dhamotharan, 2016;Lo, 2018;Yousef et al, 2013). For instance, based on a survey of 250 Malaysian ESL teachers from 25 schools located in both urban and rural areas, Lo (2018) found that the rural ESL teachers' WTC in English was significantly lower than that of urban ESL teachers in group discussion, interpersonal communication, public speaking, and talking in meetings. In a similar vein, Fahim and Dhamotharan (2016) also surveyed Malaysian ESL teachers' WTC, but their investigation focus was on pre-service teachers rather than in-service teachers and they found that the pre-service teachers achieved only a moderate level of WTC in English before becoming in-service teachers.…”
Section: Teachers' Wtc In Englishmentioning
confidence: 99%